EFFECT OF PRUNING AND ORGANIC FERTILIZATION OVER PRODUCTIVE PARAMETERS OF FOUR MEXICAN PROVENANCES OF Jatropha curcas L. - Rodriguez, Ofelia Andrea Valdes-; Gomez-Zuniga, Izteotl; Palacios-Wassenaar, Olivia Margarita; Quintas, Gabina Sol; Perez-Vazquez, Arturo (Emirates Journal of Food and Agriculture, 2020)
The performance of Mexican provenances of Jatropha curcas L. under different agropractices has not been very widely investigated in their center of origin. The purpose of this study was to determine the flowering, fruit and seed production performance of four Mexican provenances of J. curcas to pruning and organic fertilization. The evaluated provenances were obtained from the municipalities of Actopan, Tamiahua, Papantla and Amatlán located in southeastern, Mexico. The experimental design considered two factors: provenance and treatment. The treatments were bokashi, vermicompost, pruning, and the control, each one with five individuals per provenance (80 plants). Plants were monitored every week during one productive cycle (April 2016 to January 2017), starting with the development of inflorescences until the harvesting of mature fruits. The seeds obtained from the fruits were dried and weighted to determine plant productivity. The analysis of variance was performed with a significant level of 0.05. Results indicated statistically significant differences between treatments and provenances, but there was no interaction between provenances and treatments. Application of bokashi and vermicompost was statistically similar and allowed the highest productivity, Actopan had the highest productivity (436 g of dried seed by plant), which was 26 % over the control, pruning allowed the highest fruit mooring, but it delayed production by two months, which reduced the total seed productivity (297 g by plant), being statistically similar to the control. We conclude that Mexican provenances have a positive response to organic fertilization and pruning, but pruning reduces its productive period.